Otitis media with antineutrophil cytoplasmic antibody-associated vasculitis caused by Eustachian tube inflammation. Issue 2 (3rd July 2018) - Nakamura, Kaito; Hattori, Koto; Nishiwaki, Aya; Kashiwakuma, Daisuke; Ando, Yuji; Isogai, Jun; Kagami, Shin-Ichiro
Abstract: A 78-year-old woman with a 9-year history of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis presented with malaise and loss of appetite for one month. Laboratory tests showed an increased serum C-reactive protein level and a high titer of serum myeloperoxidase-specific ANCA. Computed tomography (CT) scan showed thickening of the mucosa of the left Eustachian tube. Although she did not complain of difficulty in hearing, results of audiometry showed left conductive hearing loss. She was diagnosed to have otitis media. The otitis media did not respond to antibiotics. For further evaluation of the Eustachian tube lesion, we performed magnetic resonance imaging (MRI), which revealed abnormal enhancement and swelling of the left Eustachian tube; this suggested that there was an obstruction of the Eustachian tube. Following the diagnosis of otitis media with ANCA-associated vasculitis (OMAAV), treatment with prednisolone and rituximab was administered. She responded well to the treatment and recovered her hearing. Although increased attention has been focused on OMAAV in recent years, the mechanism of development of otitis media in OMAAV remains unclear. ANCA-associated vasculitis can cause Eustachian tube inflammation and obstruction, which leads to the development of otitis media. Although there are other expected mechanisms of the development of otitis media in OMAAV, Eustachian tube inflammation could be one of the mechanisms. CT scan and MRI are useful for the detection of otitis media and Eustachian tube inflammation, even when a patient is not able to notice or complain of hearing problem.